Discrete Mathematics - Proofs

Post on 01-Dec-2014

16.244 views 6 download

description

Proof techniques, proof by contradiction, mathematical induction.

Transcript of Discrete Mathematics - Proofs

Discrete MathematicsProofs

H. Turgut Uyar Aysegul Gencata Yayımlı Emre Harmancı

2001-2013

License

c©2001-2013 T. Uyar, A. Yayımlı, E. Harmancı

You are free:

to Share – to copy, distribute and transmit the work

to Remix – to adapt the work

Under the following conditions:

Attribution – You must attribute the work in the manner specified by the author or licensor (but not in anyway that suggests that they endorse you or your use of the work).

Noncommercial – You may not use this work for commercial purposes.

Share Alike – If you alter, transform, or build upon this work, you may distribute the resulting work onlyunder the same or similar license to this one.

Legal code (the full license):http://creativecommons.org/licenses/by-nc-sa/3.0/

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Brute Force Method

examining all possible cases one by one

Theorem

Every number from the set {2, 4, 6, . . . , 26} can be writtenas the sum of at most 3 square numbers.

Proof.2 = 1+1 10 = 9+1 20 = 16+44 = 4 12 = 4+4+4 22 = 9+9+46 = 4+1+1 14 = 9+4+1 24 = 16+4+48 = 4+4 16 = 16 26 = 25+1

18 = 9+9

Brute Force Method

examining all possible cases one by one

Theorem

Every number from the set {2, 4, 6, . . . , 26} can be writtenas the sum of at most 3 square numbers.

Proof.2 = 1+1 10 = 9+1 20 = 16+44 = 4 12 = 4+4+4 22 = 9+9+46 = 4+1+1 14 = 9+4+1 24 = 16+4+48 = 4+4 16 = 16 26 = 25+1

18 = 9+9

Brute Force Method

examining all possible cases one by one

Theorem

Every number from the set {2, 4, 6, . . . , 26} can be writtenas the sum of at most 3 square numbers.

Proof.2 = 1+1 10 = 9+1 20 = 16+44 = 4 12 = 4+4+4 22 = 9+9+46 = 4+1+1 14 = 9+4+1 24 = 16+4+48 = 4+4 16 = 16 26 = 25+1

18 = 9+9

Basic Rules

Universal Specification (US)

∀x p(x) ⇒ p(a)

Universal Generalization (UG)

p(a) for an arbitrarily chosen a ⇒ ∀x p(x)

Basic Rules

Universal Specification (US)

∀x p(x) ⇒ p(a)

Universal Generalization (UG)

p(a) for an arbitrarily chosen a ⇒ ∀x p(x)

Universal Specification Example

Example

All humans are mortal. Socrates is human.Therefore, Socrates is mortal.

U : all humans

p(x): x is mortal

∀x p(x): All humans are mortal.

a: Socrates, a ∈ U : Socrates is human.

therefore, p(a): Socrates is mortal.

Universal Specification Example

Example

All humans are mortal. Socrates is human.Therefore, Socrates is mortal.

U : all humans

p(x): x is mortal

∀x p(x): All humans are mortal.

a: Socrates, a ∈ U : Socrates is human.

therefore, p(a): Socrates is mortal.

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Vacuous Proof

vacuous proof

to prove P ⇒ Q, show that P is false

Vacuous Proof Example

Theorem

∀S [∅ ⊆ S ]

Proof.

∅ ⊆ S ⇔ ∀x [x ∈ ∅ → x ∈ S ]∀x [x /∈ ∅]

Vacuous Proof Example

Theorem

∀S [∅ ⊆ S ]

Proof.

∅ ⊆ S ⇔ ∀x [x ∈ ∅ → x ∈ S ]∀x [x /∈ ∅]

Vacuous Proof Example

Theorem

∀S [∅ ⊆ S ]

Proof.

∅ ⊆ S ⇔ ∀x [x ∈ ∅ → x ∈ S ]∀x [x /∈ ∅]

Trivial Proof

trivial proof

to prove P ⇒ Q, show that Q is true

Trivial Proof Example

Theorem

∀x ∈ R [x ≥ 0 ⇒ x2 ≥ 0]

Proof.

∀x ∈ R [x2 ≥ 0]

Trivial Proof Example

Theorem

∀x ∈ R [x ≥ 0 ⇒ x2 ≥ 0]

Proof.

∀x ∈ R [x2 ≥ 0]

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Direct Proof

direct proof

to prove P ⇒ Q, show that P ` Q

Direct Proof Example

Theorem

∀a ∈ Z [3|(a− 2) ⇒ 3|(a2 − 1)]

Proof.

3|(a− 2) ⇒ ∃k ∈ N [a− 2 = 3k]

⇒ a + 1 = a− 2 + 3 = 3k + 3 = 3(k + 1)

⇒ a2 − 1 = (a + 1)(a− 1) = 3(k + 1)(a− 1)

Direct Proof Example

Theorem

∀a ∈ Z [3|(a− 2) ⇒ 3|(a2 − 1)]

Proof.

3|(a− 2) ⇒ ∃k ∈ N [a− 2 = 3k]

⇒ a + 1 = a− 2 + 3 = 3k + 3 = 3(k + 1)

⇒ a2 − 1 = (a + 1)(a− 1) = 3(k + 1)(a− 1)

Direct Proof Example

Theorem

∀a ∈ Z [3|(a− 2) ⇒ 3|(a2 − 1)]

Proof.

3|(a− 2) ⇒ ∃k ∈ N [a− 2 = 3k]

⇒ a + 1 = a− 2 + 3 = 3k + 3 = 3(k + 1)

⇒ a2 − 1 = (a + 1)(a− 1) = 3(k + 1)(a− 1)

Direct Proof Example

Theorem

∀a ∈ Z [3|(a− 2) ⇒ 3|(a2 − 1)]

Proof.

3|(a− 2) ⇒ ∃k ∈ N [a− 2 = 3k]

⇒ a + 1 = a− 2 + 3 = 3k + 3 = 3(k + 1)

⇒ a2 − 1 = (a + 1)(a− 1) = 3(k + 1)(a− 1)

Indirect Proof

indirect proof

to prove P ⇒ Q, show that ¬Q ` ¬P

Indirect Proof Example

Theorem

∀x , y ∈ N [x · y > 25 ⇒ (x > 5) ∨ (y > 5)]

Proof.

¬Q ⇔ (0 ≤ x ≤ 5) ∧ (0 ≤ y ≤ 5)

x · y ≤ 5 · 5 = 25

Indirect Proof Example

Theorem

∀x , y ∈ N [x · y > 25 ⇒ (x > 5) ∨ (y > 5)]

Proof.

¬Q ⇔ (0 ≤ x ≤ 5) ∧ (0 ≤ y ≤ 5)

x · y ≤ 5 · 5 = 25

Indirect Proof Example

Theorem

∀x , y ∈ N [x · y > 25 ⇒ (x > 5) ∨ (y > 5)]

Proof.

¬Q ⇔ (0 ≤ x ≤ 5) ∧ (0 ≤ y ≤ 5)

x · y ≤ 5 · 5 = 25

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Proof by Contradiction

proof by contradiction

to prove P, show that ¬P ` Q ∧ ¬Q

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Equivalence Proofs

to prove P ⇔ Q, both P ⇒ Q and Q ⇒ P must be proven

a method to prove P1 ⇔ P2 ⇔ · · · ⇔ Pn:P1 ⇒ P2 ⇒ · · · ⇒ Pn ⇒ P1

Equivalence Proofs

to prove P ⇔ Q, both P ⇒ Q and Q ⇒ P must be proven

a method to prove P1 ⇔ P2 ⇔ · · · ⇔ Pn:P1 ⇒ P2 ⇒ · · · ⇒ Pn ⇒ P1

Equivalence Proof Example

Theorem

a, b, n, q1, r1, q2, r2 ∈ Z+

a = q1 · n + r1b = q2 · n + r2

r1 = r2 ⇔ n|(a− b)

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Equivalence Proof Example

Theorem

A ⊆ B

⇔ A ∪ B = B

⇔ A ∩ B = A

⇔ B ⊆ A

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Equivalence Proof Example

B ⊆ A ⇒ A ⊆ B.

¬(A ⊆ B) ⇒ ∃w [w ∈ A ∧ w /∈ B]

⇒ ∃w [w /∈ A ∧ w ∈ B]

⇒ ¬(B ⊆ A)

Equivalence Proof Example

B ⊆ A ⇒ A ⊆ B.

¬(A ⊆ B) ⇒ ∃w [w ∈ A ∧ w /∈ B]

⇒ ∃w [w /∈ A ∧ w ∈ B]

⇒ ¬(B ⊆ A)

Equivalence Proof Example

B ⊆ A ⇒ A ⊆ B.

¬(A ⊆ B) ⇒ ∃w [w ∈ A ∧ w /∈ B]

⇒ ∃w [w /∈ A ∧ w ∈ B]

⇒ ¬(B ⊆ A)

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Induction

Definition

S(n): a predicate defined on n ∈ Z+

S(n0) ∧ (∀k ≥ n0 [S(k) ⇒ S(k + 1)]) ⇒ ∀n ≥ n0 S(n)

S(n0): base step

∀k ≥ n0 [S(k) ⇒ S(k + 1)]: induction step

Induction

Definition

S(n): a predicate defined on n ∈ Z+

S(n0) ∧ (∀k ≥ n0 [S(k) ⇒ S(k + 1)]) ⇒ ∀n ≥ n0 S(n)

S(n0): base step

∀k ≥ n0 [S(k) ⇒ S(k + 1)]: induction step

Induction

Definition

S(n): a predicate defined on n ∈ Z+

S(n0) ∧ (∀k ≥ n0 [S(k) ⇒ S(k + 1)]) ⇒ ∀n ≥ n0 S(n)

S(n0): base step

∀k ≥ n0 [S(k) ⇒ S(k + 1)]: induction step

Induction

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Induction Example

Theorem

∀n ∈ Z+, n ≥ 4 [2n < n!]

Proof.

n = 4: 24 = 16 < 24 = 4!

n = k: assume 2k < k!

n = k + 1:2k+1 = 2 · 2k < 2 · k! < (k + 1) · k! = (k + 1)!

Induction Example

Theorem

∀n ∈ Z+, n ≥ 4 [2n < n!]

Proof.

n = 4: 24 = 16 < 24 = 4!

n = k: assume 2k < k!

n = k + 1:2k+1 = 2 · 2k < 2 · k! < (k + 1) · k! = (k + 1)!

Induction Example

Theorem

∀n ∈ Z+, n ≥ 4 [2n < n!]

Proof.

n = 4: 24 = 16 < 24 = 4!

n = k: assume 2k < k!

n = k + 1:2k+1 = 2 · 2k < 2 · k! < (k + 1) · k! = (k + 1)!

Induction Example

Theorem

∀n ∈ Z+, n ≥ 4 [2n < n!]

Proof.

n = 4: 24 = 16 < 24 = 4!

n = k: assume 2k < k!

n = k + 1:2k+1 = 2 · 2k < 2 · k! < (k + 1) · k! = (k + 1)!

Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = k: assume k = 3i + 8j

n = k + 1:

k = 3i + 8j , j > 0 ⇒ k + 1 = k − 8 + 3 · 3⇒ k + 1 = 3(i + 3) + 8(j − 1)k = 3i + 8j , j = 0, i ≥ 5 ⇒ k + 1 = k − 5 · 3 + 2 · 8⇒ k + 1 = 3(i − 5) + 8(j + 2)

Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = k: assume k = 3i + 8j

n = k + 1:

k = 3i + 8j , j > 0 ⇒ k + 1 = k − 8 + 3 · 3⇒ k + 1 = 3(i + 3) + 8(j − 1)k = 3i + 8j , j = 0, i ≥ 5 ⇒ k + 1 = k − 5 · 3 + 2 · 8⇒ k + 1 = 3(i − 5) + 8(j + 2)

Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = k: assume k = 3i + 8j

n = k + 1:

k = 3i + 8j , j > 0 ⇒ k + 1 = k − 8 + 3 · 3⇒ k + 1 = 3(i + 3) + 8(j − 1)k = 3i + 8j , j = 0, i ≥ 5 ⇒ k + 1 = k − 5 · 3 + 2 · 8⇒ k + 1 = 3(i − 5) + 8(j + 2)

Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = k: assume k = 3i + 8j

n = k + 1:

k = 3i + 8j , j > 0 ⇒ k + 1 = k − 8 + 3 · 3⇒ k + 1 = 3(i + 3) + 8(j − 1)k = 3i + 8j , j = 0, i ≥ 5 ⇒ k + 1 = k − 5 · 3 + 2 · 8⇒ k + 1 = 3(i − 5) + 8(j + 2)

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Strong Induction

Definition

S(n0) ∧ (∀k ≥ n0 [(∀i ≤ k S(i)) ⇒ S(k + 1)]) ⇒ ∀n ≥ n0 S(n)

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = 15: 15 = 3 · 5 + 8 · 0n = 16: 16 = 3 · 0 + 8 · 2n ≤ k: assume k = 3i + 8j

n = k + 1: k + 1 = (k − 2) + 3

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = 15: 15 = 3 · 5 + 8 · 0n = 16: 16 = 3 · 0 + 8 · 2n ≤ k: assume k = 3i + 8j

n = k + 1: k + 1 = (k − 2) + 3

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = 15: 15 = 3 · 5 + 8 · 0n = 16: 16 = 3 · 0 + 8 · 2n ≤ k: assume k = 3i + 8j

n = k + 1: k + 1 = (k − 2) + 3

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = 15: 15 = 3 · 5 + 8 · 0n = 16: 16 = 3 · 0 + 8 · 2n ≤ k: assume k = 3i + 8j

n = k + 1: k + 1 = (k − 2) + 3

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Flawed Induction Example

Flawed Induction Example

Theorem

All horses are of the same color.

A(n): All horses in sets of n horses are of the same color.

∀n ∈ N+ A(n)

Flawed Induction Example

Theorem

All horses are of the same color.

A(n): All horses in sets of n horses are of the same color.

∀n ∈ N+ A(n)

Flawed Induction Example

invalid induction step

n = 1: A(1)All horses in sets of 1 horse are of the same color.

n = k: assume A(k) is trueAll horses in sets of k horses are of the same color.

A(k + 1) = {a1, a2, . . . , ak} ∪ {a2, a3, . . . , ak+1}All horses in set {a1, a2, . . . , ak} are of the same color (a2).All horses in set {a2, a3, . . . , ak+1} are of the same color (a2).

Flawed Induction Example

invalid induction step

n = 1: A(1)All horses in sets of 1 horse are of the same color.

n = k: assume A(k) is trueAll horses in sets of k horses are of the same color.

A(k + 1) = {a1, a2, . . . , ak} ∪ {a2, a3, . . . , ak+1}All horses in set {a1, a2, . . . , ak} are of the same color (a2).All horses in set {a2, a3, . . . , ak+1} are of the same color (a2).

Flawed Induction Example

invalid induction step

n = 1: A(1)All horses in sets of 1 horse are of the same color.

n = k: assume A(k) is trueAll horses in sets of k horses are of the same color.

A(k + 1) = {a1, a2, . . . , ak} ∪ {a2, a3, . . . , ak+1}All horses in set {a1, a2, . . . , ak} are of the same color (a2).All horses in set {a2, a3, . . . , ak+1} are of the same color (a2).

Flawed Induction Examples

References

Required Reading: Grimaldi

Chapter 2: Fundamentals of Logic

2.5. Quantifiers, Definitions, and the Proofs of Theorems

Chapter 4: Properties of Integers: Mathematical Induction

4.1. The Well-Ordering Principle: Mathematical Induction

Supplementary Reading: O’Donnell, Hall, Page

Chapter 4: Induction